PTERIDOPHYTES OF ALAS PURWO NATIONAL PARK AND THEIR MEDICINAL POTENCY - Fuad Bahrul Ulum; Dwi Setyati (UNEJ e-Proceeding, 2016)
An investigation of Pteridophytes diversity at Alas Puwo National Park, Banyuwangi, East Java Province, Indonesia, was carried out in November 2015. A total 10 species of Ferns fom from 6 families had been identified based on their morphological chracteristic. The species are: Stenochlaena palustris, Cyathea bipinnatifida, Lygodium circinatum, Drynaria quercifolia, Pteris vittata, Cyclosorus aridus, Christella dentate, Pneumatopteris costata, Sphaerostephanos invisus, and Amauropelta bergiana.The medicinal potency from all speciments had been observed based on literature study. Only 5 Species has medicinal poterncy mainly for antimicrobial, wound treatment, and to treat fever.